Capacitor voltages balancing method for buck modular DC/DC converter - Firas Abdul-hadi Salih; Turki Kahawish Hassan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The most critical problem of the modular DC-DC converter (MDCC) is the voltage balancing of the submodule (SM) capacitors, the MDCC with stepped 2-level modulation has been developed and presents a good solution, however, this type of modulation has many restrictions when there is a wide range of capacitance tolerance of the SM capacitors that results inaccurate capacitor voltages balancing. To solve this problem, this paper discusses a proposed method of capacitor voltage balancing. Compared with stepped 2-level modulation, the voltage balancing method using modified duty cycle modulation offers the merits: i) reduction in output voltage and SM capacitor voltages overshoot during dynamic operation and improvement in the time response of the system and; ii) accurate voltage balancing over wide range of capacitance tolerance of each SM capacitor; and iii) the sorting algorithm replaced with modified duty cycle modulation method for the SM capacitor voltages balancing which reduces the computation burden. The proposed method ensures a stable voltage balancing, improves the time response of the system, and decreases the voltage and current overshoot during the dynamic response compared with prior art of MDCCs, where the stepped 2-level modulation is adopted. An analytical simulation of the MDCC is presented using MATLAB/Simulink to explain the operation.